Modified montmorillonite nanolayers for nano-encapsulation of biomolecules - Mozhgan Akbari Alavijeh; Mehdi Nasiri Sarvi; Zahra Ramazani Afarani (Heliyon, 2019)
Vitamin B6 was nano-encapsulated in between modified montmorillonite nanolayers. Results indicated that electrostatic interaction forces dominate the adsorption onto different sites of the nanolayers. The successful nano-encapsulation was achieved when the interlayers spaces of the nanolayer were saturated with cations of Na+ or Ca2+ resulted in adsorption of vitamin B6 in between nanosheets. At these conditions, controlled pH-responsive desorption properties were detected and vitamin B6 was released mostly from the interlayer spaces. The presented modified montmorillonite could be used for nanoencapsulation of drugs and biomolecules with high protection of carrying materials during storage and even through the digestion process.